Proximity and shared governance? Obstacles and organisational tensions in YG program in Portugal - Ferreira, Tatiana (2021)
Following the last global economic crisis, one of the major structural problems Europe had to face was the substantial rise in unemployment rates. In particular, young people, on the one hand, and the contexts where the financial crisis was more intense and even led to external intervention, such as Portugal, Greece, Ireland and to a lesser extent, Italy and Spain, on the other, were considerably affected. Such rise in youth unemployment rate contributed significantly to a simultaneous increase in the number of young people not in education, employment or training (NEET), which have been monitored for some time as one of the major risks affecting contemporary young population. The idea that young people were increasingly disconnected from the major inclusion social structures, such as education and employment, motivated the building up of the EU largest policy and financial package in the field of employment, the Youth Guarantee Program (YG), launched in 2013 and implemented by each member state according to each country specificity. Expected to last until 2020, the program was aimed at ensuring all young people under the age of 25 years (in some cases, like the Portuguese one, the limit was raised to 29 years) receive a good quality offer of employment, continued education, apprenticeship or traineeship within a period of four months of becoming unemployed or leaving formal education. Although rooted in the field of employment, the program underlines the importance of education, stressing the idea that young people could and should receive appropriate educational and training offers in order to enhance their present and future employability, especially for those whose trajectories are marked with school failure and dropout.